Computational Thinking Approach in Physics Experiment Based on Excel-VBA (Visual Basic for Applications) - Fayanto, Suritno; Sukariasih, Luh; Sahara, La; Lis, Lis; Miherani, Miherani (Proceeding International Conference on Religion, Science and Education, 2025)
This study emphasizes the importance of computational thinking skills (CTS) in physics education. The urgency of the study lies in the need to strengthen students' problem-solving abilities through the CTS approach using technologies such as Excel-VBA (Visual Basic for Applications) for scientific simulations. This study aimed to explore the use of Excel-VBA in physics learning, especially in the phenomena of stationary waves and damped harmonic oscillations. The method used was an experimental design involving students and one instructor. Data were collected through students' work in physics simulations using Excel-VBA. Data analysis was carried out by evaluating students' work in designing algorithms, performing basic programming, and verifying the results of the simulations that had been made. The results showed that students could create basic simulations of physics phenomena with Excel-VBA, which can support students' understanding of complex concepts. The simulations created include visualizations of stationary waves and damped harmonic oscillations adjusted to different variables. This study concludes that the use of Excel-VBA based on computational thinking skills can facilitate students' understanding of programming concepts and their applications in physics. This paper implies that Excel-VBA can be an interesting and practical alternative learning media to support the understanding of complex science concepts and encourage the development of basic programming skills among students.